Clinical evaluation of a real-time optoelectronic device in cervical cancer screening. (November 2021) - Wei, Yingting; Wang, Wenjing; Cheng, Mengxing; Hong, Zubei; Gu, Liying; Niu, Jiaxin; Di, Wen; Qiu, Lihua
Abstract: Objective: Early screening and intervention are crucial for the prevention and treatment of cervical cancer. TruScreen is a real-time, intelligent, pathological diagnostic technology designed for cervical cancer screening. The aim of this study was to evaluate the clinical value of TruScreen in screening for cervical lesions. Study design: A total of 458 women aged between 25 and 65 years were recruited to receive cervical cancer screening, including human papillomavirus (HPV) testing, cytological testing using the ThinPrep cytology test (TCT), and TruScreen from December 2018 to January 2020. The clinical performance of TruScreen, alone and in combination with HPV testing, was evaluated to detect cervical intraepithelial neoplasia grade 2 or worse (CIN2+ or CIN3+). Results: For detection of CIN2+, the sensitivity and specificity of TruScreen were 83.78% and 78.86%, respectively. The specificity of TruScreen was significantly higher than those of HPV testing (50.59%, P < 0.001) and TCT (55.58%, P < 0.001). In high-risk HPV-positive women, the specificity of HPV testing combined with TruScreen was significantly higher than that of HPV testing combined with TCT (50% vs 39.9%, P = 0.004). The sensitivity of HPV testing combined with TruScreen was comparable to that of HPV testing combined with TCT (93.94% vs 87.88%, P = 0.625). Similar patterns were also observed for CIN3+ cases. Conclusion: TruScreen has the potential for screening high-grade cervical precancerous lesions and may replace cytological tests as a cervical cancer screening method in China to avoid subjectivity in the interpretation of cytological tests and requirements by pathologists.